2016
DOI: 10.3390/rs8020163
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Soil Alkalinity and Salinity in the Wuyu’er-Shuangyang River Basin, Northeast China

Abstract: Abstract:The Songnen Plain of the Northeast China is one of the three largest soda saline-alkali regions worldwide. To better understand soil alkalinization and salinization in this important agricultural region, it is vital to explore the distribution and variation of soil alkalinity and salinity in space and time. This study examined soil properties and identified the variables to extract soil alkalinity and salinity via physico-chemical, statistical, spectral, and image analysis. The physico-chemical and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 29 publications
(22 reference statements)
1
42
0
2
Order By: Relevance
“…There is a positive and significant correlation between pH and EC (r = 0.57; p≤0.01) pH and Na + (r =0.59; p≤0.01) and Cl − (r =0.63) and SO 4 2− (r = 0.51) signifying that the pH of the soil is primarily influenced by the Cl − and SO 4 2− content (Table 2). Bai et al, (2016) also reported positive correlation between pH and EC and Na + ions in the Wuyu'er-Shuangyang River Basin, Northeast China. The pH variation in the area is small as indicated by low CV which can be attributed to high buffering capacity of the soils and absence of carbonates in the saturation extract (Sharma and Gupta, 1986).…”
Section: Soil Phmentioning
confidence: 79%
See 1 more Smart Citation
“…There is a positive and significant correlation between pH and EC (r = 0.57; p≤0.01) pH and Na + (r =0.59; p≤0.01) and Cl − (r =0.63) and SO 4 2− (r = 0.51) signifying that the pH of the soil is primarily influenced by the Cl − and SO 4 2− content (Table 2). Bai et al, (2016) also reported positive correlation between pH and EC and Na + ions in the Wuyu'er-Shuangyang River Basin, Northeast China. The pH variation in the area is small as indicated by low CV which can be attributed to high buffering capacity of the soils and absence of carbonates in the saturation extract (Sharma and Gupta, 1986).…”
Section: Soil Phmentioning
confidence: 79%
“…Vadivelu et al, (2001) also reported positive significant correlation between available K and organic carbon and clay. Under saline and sodic soils, K fertilization management may need to be altered because of potassium competition with other cations especially Na + in the plant and to the effects of salinity in K reactions in soil (Bar-Tal et al, 1991). The coefficient of variation varied sharply with depth indicating lateral and vertical variation.…”
Section: Available Potassium (K)mentioning
confidence: 99%
“…Due to the human activities, climate, geology, and terrain conditions, these mid-latitude semi-arid grasslands are salinized and alkalized at various degrees [32][33][34]. As a result, the Songnen grasslands are at different succession stages with diverse community compositions and, hence, show a typically heterogeneous landscape.…”
Section: Test Areamentioning
confidence: 99%
“…There is renewed interest in the use of broadband multispectral imagery for regional soil salt content prediction (e.g., [4,5,[9][10][11][12][13][14][15][16]). Generally, these studies include (1) the bands' selection and investigation of spectral indices, including salinity indices and vegetation indices (e.g., [12,13]); (2) the optimized combination of bands and spectral indices for modeling, such as [4,5,14]; and (3) the long-term soil salinity dynamic analysis, such as in References [15,16].…”
Section: Introductionmentioning
confidence: 99%